Diversity in Protected Area Governance and Its Implications for Management: An Institutional Analysis of Selected Parks in Iceland - Jukka Siltanen; Jon Geir Petursson; David Cook; Brynhildur Davidsdottir (Land, 2022)
A protected area (PA) is essentially a governance system, a spatially defined area encompassing natural and/or cultural attributes, governed by a set of actors with different roles and institutional frameworks. There are many types of PA governance systems, guided by historical-, site-specific- and context-dependent factors. This study has the objective to advance understanding of PA governance systems, their diversity and the implications for management. We take the case of Iceland and five of its major PAs. We develop an analytical framework for the study of PA governance systems, investigating their evolutionary trajectories, conducting a comparative institutional analysis of their environmental governance systems (EGS), and assessing their management implications using nature-based tourism as a key variable. We find this framework effective and applicable beyond this study. We find great diversity in the five PA governance systems that has not come by chance but deliberately negotiated in their protracted establishment trajectories. At the individual park level, such PA diversity can be embraced as a sign of an adaptive approach to governance instead of a one-size-fits-all solution while at the national level, however, such fragmentation constitutes coordination challenges. Our analysis of the current portfolio of PA governance systems reveals they accommodate most of the needed management measures, but a problem remains concerning scattered and locked-in individual governance systems that do not support coordinated action and sharing of expertise and resources. This calls upon policy guidance with more formal coordination, such as a legal and national policy framework embracing PA governance diversity, but also securing more coordinated measures for day-to-day management.